A hemostatic material and preparation method thereof

By acidizing the oxidized regenerated cellulose and compounding it with Cu2+-loaded oxidized nanocellulose, a new hemostatic material was prepared, which solved the problem of the long halt time of existing hemostatic materials and may damage the nervous system, achieving a rapid and effective hemostatic effect.

CN116271195BActive Publication Date: 2025-03-18THE FIRST MEDICAL CENT CHINESE PLA GENERAL HOSPITAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310511037.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-08
Publication Date
2025-03-18
Estimated Expiration
2043-05-08

AI Technical Summary

Technical Problem

The existing hemostatic materials have a long time to stop bleeding when treating wounds, and the hemostatic effect is not ideal, and there is a risk of damage to the human nervous system.

Method used

A new hemostatic material was prepared by acidizing the oxidized regenerated cellulose containing sodium carboxylate structure, compounding it with Cu2+-loaded oxidized nanocellulose, and then processing it in a PBS solution containing thrombin.

Benefits of technology

The hemostasis time of this hemostasis material is significantly shortened, with an average hemostasis time of 2.5 to 3.0 minutes, which has better hemostasis effect and reduces the potential risk of damage to the human nervous system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004218492900000091
    Figure BDA0004218492900000091
  • Figure BDA0004218492900000101
    Figure BDA0004218492900000101
Patent Text Reader

Abstract

The present invention provides a hemostatic material and a preparation method thereof, and belongs to the technical field of biomedical composite materials. The preparation method of the hemostatic material provided by the present invention comprises the following steps: (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid and then performing an acidification treatment to obtain acidified oxidized regenerated cellulose; (2) impregnating the oxidized nanocellulose into a copper salt solution to obtain a Cu-loaded nanocellulose; 2+ (3) the acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) 2+ The oxidized nanocellulose is added to a PBS solution containing thrombin and mixed, and then washed and dried in sequence to obtain a hemostatic material. The results of the embodiment show that the average hemostatic time of the hemostatic material prepared by the preparation method provided by the present invention is 2.5 to 3.0 minutes, the hemostatic time is short, and the hemostatic effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical composite materials, and in particular to a hemostatic material and a preparation method thereof. Background Art

[0002] Biomedical materials are a class of high-tech materials developed in the past three decades, among which hemostatic materials have gradually attracted the attention of the medical community. With the rapid development of modern science and technology, the research on hemostatic materials has made very rapid progress, various new hemostatic materials have continuously appeared, and the performance has also been greatly improved. At present, commonly used local hemostatic materials include fibrin glue, thrombin powder, gelatin sponge, collagen sponge, chitosan sponge, oxidized cellulose, microfiber collagen, alginate fiber, zeolite, cyanoacrylate, plant polysaccharide powder, etc. Biomedical hemostatic materials with definite hemostatic effect, easy use, good biocompatibility and controllable degradation rate have become the main objects of people's attention and research. Therefore, how to further improve the hemostatic performance of hemostatic materials has become a technical problem to be solved in this field. Summary of the invention

[0003] The purpose of the present invention is to provide a hemostatic material and a preparation method thereof. The hemostatic material provided by the present invention has a short hemostatic time required for treating wounds and has a better hemostatic effect.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a hemostatic material, comprising the following steps:

[0006] (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid and then performing an acidification treatment to obtain acidified oxidized regenerated cellulose;

[0007] (2) Immersing the oxidized nanocellulose in a copper salt solution to obtain a Cu-loaded 2+ of oxidized nanocellulose;

[0008] (3) the acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) 2+ The oxidized nanocellulose is added into a PBS solution containing thrombin and mixed, and then washed and dried in sequence to obtain a hemostatic material;

[0009] The preparation of step (1) and step (2) is not in any particular order.

[0010] Preferably, the content of sodium carboxylate structure in the oxidized regenerated cellulose containing sodium carboxylate structure in step (1) is 0.5-5.0 mmol / g.

[0011] Preferably, in the step (1), the molar ratio of the sodium carboxylate structure in the oxidized regenerated cellulose containing the sodium carboxylate structure to the hydrogen ions in the dilute hydrochloric acid is (10-50):1.

[0012] Preferably, the acidification treatment time in step (1) is 2 to 48 hours, and the acidification treatment temperature is 10 to 30°C.

[0013] Preferably, the copper salt solution in step (2) is a copper chloride solution or a copper sulfate solution, and the concentration of the copper salt solution is 1 to 10 mmol / L.

[0014] Preferably, the immersion temperature in step (2) is 10 to 30° C., and the immersion time is 6 to 12 hours.

[0015] Preferably, in step (3), the acidified oxidized regenerated cellulose and the loaded Cu 2+ The mass ratio of oxidized nanocellulose is (1~5):1.

[0016] Preferably, the concentration of thrombin in the PBS solution containing thrombin in step (3) is 0.01-1 g / L.

[0017] Preferably, the mixing method in step (3) is ultrasonic mixing, and the mixing time is 0.5 to 6 hours.

[0018] The present invention provides a hemostatic material prepared by the preparation method described in the above technical solution.

[0019] The present invention provides a method for preparing a hemostatic material, comprising the following steps: (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid and then performing an acidification treatment to obtain acidified oxidized regenerated cellulose; (2) immersing the oxidized nanocellulose in a copper salt solution to obtain a Cu-loaded regenerated cellulose; and 2+ (3) the acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) 2+The oxidized nanocellulose is added to a PBS solution containing thrombin and mixed, and then washed and dried in sequence to obtain a hemostatic material; the preparation of step (1) and step (2) is not in particular order. The invention performs acidification treatment on the oxidized regenerated cellulose containing sodium carboxylate structure, converts the sodium carboxylate structure part into carboxylic acid structure, and the concentration of acidified carboxylic acid functional group presents gradient distribution during the acidification process, and can still maintain the original shape, and the oxidized regenerated cellulose containing sodium carboxylate structure will not dissolve during the acidification process, and its strength meets the clinical hemostasis requirements; at the same time, in addition to the carboxylic acid functional group formed by acidification, there are also some sodium carboxylate structures, so the acidity of the hemostatic material is weaker than that of the oxidized regenerated cellulose material, which can reduce or even eliminate the possibility of causing damage to the human nervous system, thereby expanding the application range of the hemostatic material; by loading copper ions on the oxidized nanocellulose and then treating it in a PBS solution containing thrombin, not only can the thrombin factor be loaded on the hemostatic material, further improving the hemostatic performance of the hemostatic material, but also the copper ions can be converted into copper phosphate, which has a good protective effect on the stability of the organic component thrombin, and can solve the problem that thrombin is easy to inactivate and has high requirements for storage and use conditions; by compounding the oxidized regenerated cellulose and the nanocellulose, both cellulose surfaces have carboxyl groups, have dual hemostatic effects, greatly shorten the hemostatic time, and achieve the effect of rapid hemostasis. The results of the examples show that the average hemostatic time of the hemostatic material prepared by the preparation method provided by the present invention is 2.5 to 3.0 minutes, the hemostatic time is short, and the hemostatic effect is good. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing a hemostatic material, comprising the following steps:

[0021] (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid and then performing an acidification treatment to obtain acidified oxidized regenerated cellulose;

[0022] (2) Immersing the oxidized nanocellulose in a copper salt solution to obtain a Cu-loaded 2+ of oxidized nanocellulose;

[0023] (3) the acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) 2+ The oxidized nanocellulose is added into a PBS solution containing thrombin and mixed, and then washed and dried in sequence to obtain a hemostatic material;

[0024] The preparation of step (1) and step (2) is not in any particular order.

[0025] The invention mixes oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid and then performs acidification treatment to obtain acidified oxidized regenerated cellulose.

[0026] In the present invention, the content of the sodium carboxylate structure in the oxidized regenerated cellulose containing the sodium carboxylate structure is preferably 0.5 to 5.0 mmol / g, more preferably 2.0 to 3.5 mmol / g. The present invention has no special limitation on the specific source of the oxidized regenerated cellulose containing the sodium carboxylate structure, and a commercial product well known to those skilled in the art can be used, or it can be prepared by conventional methods in the art. The present invention controls the content of the sodium carboxylate structure on the oxidized regenerated cellulose, which is beneficial to control the conversion of part of the sodium carboxylate structure into carboxylic acid groups during acidification, thereby further improving the hemostatic performance of the hemostatic material.

[0027] In the present invention, the molar ratio of the sodium carboxylate structure in the oxidized regenerated cellulose containing the sodium carboxylate structure to the hydrogen ion in the dilute hydrochloric acid is preferably (10-50): 1, more preferably (20-40): 1. The present invention can further control the content of the sodium carboxylate structure converted into carboxylic acid by controlling the relationship between the amount of the sodium carboxylate structure and the hydrogen ion.

[0028] The present invention has no particular limitation on the specific concentration of the dilute hydrochloric acid, which can be determined according to the technical common sense of those skilled in the art.

[0029] In the present invention, the acid treatment time is preferably 2 to 48 hours, more preferably 6 to 36 hours, and further preferably 12 to 24 hours; the acid treatment temperature is preferably 10 to 30° C., more preferably 20 to 25° C. In the present invention, the sodium carboxylate structure in the oxidized regenerated cellulose can be further converted into a carboxylic acid group by controlling the acid treatment time.

[0030] In the present invention, the acidification treatment is preferably carried out under stirring conditions, and the stirring rate is preferably 200 to 500 r / min, more preferably 300 to 400 r / min. In the present invention, the oxidized regenerated cellulose can be fully acidified by carrying out the acidification treatment under stirring conditions.

[0031] After the acidification treatment is completed, the present invention preferably filters, washes and dries the acidification product in sequence to obtain acidified oxidized regenerated cellulose.

[0032] The present invention has no special limitation on the specific operation of the filtration, which can be determined according to the common technical knowledge in the art. In the present invention, the washing method is preferably to rinse with ethanol 2 to 5 times. In the present invention, the drying method is preferably freeze drying; the freeze drying temperature is preferably -20 to -50°C; the freeze drying time is preferably 10 to 20 hours. The present invention can remove impurities in the product by washing and drying the product.

[0033] The present invention immerses oxidized nanocellulose into a copper salt solution to obtain a loaded Cu 2+of oxidized nanocellulose.

[0034] The present invention has no particular limitation on the specific source of the oxidized nanocellulose, and a commercial product well known to those skilled in the art or self-prepared product may be used.

[0035] In the present invention, the copper salt solution is preferably a copper chloride solution or a copper sulfate solution; the concentration of the copper salt solution is preferably 1 to 10 mmol / L, more preferably 3 to 8 mmol / L. By controlling the concentration of the copper salt, the present invention can not only load a sufficient amount of copper ions on the oxidized nanocellulose, but also avoid excessive copper ion loading, which causes the hemostatic material to have a negative impact on the wound.

[0036] The present invention has no particular limitation on the dosage relationship between the oxidized nanocellulose and the copper salt solution, as long as the oxidized nanocellulose can be completely immersed in the copper salt solution.

[0037] In the present invention, the immersion temperature is preferably 10-30°C, more preferably 20-25°C; the immersion time is preferably 6-12h, more preferably 8-10h. The present invention can load sufficient copper ions on the oxidized nanocellulose by controlling the immersion parameters.

[0038] After the impregnation is completed, the present invention preferably filters, washes and dries the impregnated product in sequence to obtain the loaded Cu 2+ of oxidized nanocellulose.

[0039] The present invention has no special limitation on the specific operation of the filtration, which can be determined according to the common technical knowledge in the art. In the present invention, the washing method is preferably to soak the filtered product in distilled water for 60 to 120 seconds. The present invention has no special limitation on the operation of drying, which can dry the product. The present invention can remove impurities in the product by washing and drying the product.

[0040] Acid-oxidized regenerated cellulose and loaded Cu 2+ After the oxidation of nanocellulose, the present invention combines the acidified oxidized regenerated cellulose and the loaded Cu 2+ The oxidized nanocellulose is added to a PBS solution containing thrombin and mixed, and then washed and dried in sequence to obtain a hemostatic material.

[0041] In the present invention, the ingredients of the PBS solution preferably include Na 2 HPO 4 , KH 2 PO 4, NaCl and KCl. In the present invention, the concentration of the PBS solution is preferably 0.01-0.2 M. The present invention has no particular limitation on the specific source of the PBS solution, and a commercial product well known to those skilled in the art or self-prepared may be used.

[0042] In the present invention, the acidified oxidized regenerated cellulose and the loaded Cu 2+ The mass ratio of the oxidized nanocellulose is preferably (1-5):1, more preferably (2-4):1, and further preferably (2-3):1. 2+ The mass ratio of oxidized nanocellulose can further reduce the hemostasis time and achieve the effect of rapid hemostasis.

[0043] In the present invention, the concentration of thrombin in the PBS solution containing thrombin is preferably 0.01-1 g / L, more preferably 0.1-0.8 g / L, and further preferably 0.2-0.5 g / L. By controlling the concentration of thrombin in the PBS solution, the present invention can ensure that a sufficient amount of thrombin is loaded on the hemostatic material, thereby further improving the hemostatic effect.

[0044] The present invention is to acidify the oxidized regenerated cellulose and load Cu 2+ There is no particular limitation on the amount of oxidized nanocellulose and PBS solution containing thrombin, which can make the acidified oxidized regenerated cellulose and the loaded Cu 2+ The oxidized nanocellulose is completely immersed in the PBS solution.

[0045] In the present invention, the mixing method is preferably ultrasonic mixing; the mixing time is preferably 0.5 to 6 hours, more preferably 1 to 2 hours. The present invention can completely disperse cellulose in the solution through ultrasonic mixing, so that the acidified oxidized regenerated cellulose and the loaded Cu 2+ The oxidized nanocellulose is fully compounded and can improve the loading efficiency of thrombin.

[0046] The invention performs acidification treatment on the oxidized regenerated cellulose containing sodium carboxylate structure, converts the sodium carboxylate structure part into carboxylic acid structure, and the concentration of acidified carboxylic acid functional group presents gradient distribution during the acidification process, and can still maintain the original shape, and the oxidized regenerated cellulose containing sodium carboxylate structure will not dissolve during the acidification process, and its strength meets the clinical hemostasis requirements; at the same time, in addition to the carboxylic acid functional group formed by acidification, there are also some sodium carboxylate structures, so the acidity of the hemostatic material is weaker than that of the oxidized regenerated cellulose material, which can reduce or even eliminate the possibility of causing damage to the human nervous system, thereby expanding the application range of the hemostatic material; by loading copper ions on the oxidized nanocellulose and then treating it in a PBS solution containing thrombin, not only can the thrombin factor be loaded on the hemostatic material, further improving the hemostatic performance of the hemostatic material, but also the copper ions can be converted into copper phosphate, which has a good protective effect on the stability of the organic component thrombin, and can solve the problem that thrombin is easy to inactivate and has high requirements for storage and use conditions; by compounding the oxidized regenerated cellulose and the nanocellulose, both cellulose surfaces have carboxyl groups, have dual hemostatic effects, greatly shorten the hemostatic time, and achieve the effect of rapid hemostasis.

[0047] The present invention also provides a hemostatic material prepared by the preparation method described in the above technical solution.

[0048] In the present invention, the specific surface area of ​​the hemostatic material is preferably 4 to 50 m 2 / g, more preferably 10 to 40 m 2 / g, more preferably 20 to 35 m 2 / g; the bulk density of the hemostatic material is preferably 0.02 to 0.06 g / cm 3 , more preferably 0.03 to 0.05 g / cm 3 The hemostatic material provided by the present invention has a short hemostatic time and a high hemostatic effect.

[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] A method for preparing a hemostatic material comprises the following steps:

[0052] (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid, performing an acidification treatment under stirring conditions, and then filtering, washing and drying in sequence to obtain acidified oxidized regenerated cellulose; the content of the sodium carboxylate structure in the oxidized regenerated cellulose containing a sodium carboxylate structure is 3.0 mmol / g; the molar ratio of the sodium carboxylate structure in the oxidized regenerated cellulose containing a sodium carboxylate structure to the hydrogen ion in the dilute hydrochloric acid is 35:1; the acidification time is 12 h, the acidification temperature is 20° C.; the stirring rate is 300 r / min; the washing method is rinsing with anhydrous ethanol for 2 to 5 times; the drying method is freeze drying; the freeze drying temperature is -40° C., and the freeze drying time is 12 h;

[0053] (2) The oxidized nanocellulose is immersed in a copper salt solution, and after the immersion, it is filtered, washed and dried in sequence to obtain a Cu-loaded nanocellulose. 2+ The oxidized nanocellulose is prepared by: the copper salt solution is a copper chloride solution, and the concentration of the copper salt solution is 6 mmol / L; the immersion temperature is 25° C., and the immersion time is 12 h; the washing method is immersing in distilled water for 90 s;

[0054] (3) the acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) 2+ The oxidized nanocellulose is added to a PBS solution containing thrombin and then washed and dried in sequence to obtain a hemostatic material; the acidified oxidized regenerated cellulose and the loaded Cu 2+ The mass ratio of oxidized nanocellulose is 4:1; the concentration of thrombin in the PBS solution containing thrombin is 0.5 g / L; the mixing method is ultrasonic mixing, and the mixing time is 2 hours.

[0055] Example 2

[0056] A method for preparing a hemostatic material comprises the following steps:

[0057] (1) mixing oxidized regenerated cellulose containing sodium carboxylate structure with dilute hydrochloric acid, performing acidification treatment under stirring conditions, and then filtering, washing and drying in sequence to obtain acidified oxidized regenerated cellulose; the content of sodium carboxylate structure in the oxidized regenerated cellulose containing sodium carboxylate structure is 4.0 mmol / g; the molar ratio of sodium carboxylate structure to hydrogen ion in dilute hydrochloric acid in the oxidized regenerated cellulose containing sodium carboxylate structure is 30:1; the acidification time is 12 h, the acidification temperature is 20° C.; the stirring rate is 300 r / min; the washing method is rinsing with anhydrous ethanol for 2 to 5 times; the drying method is freeze drying; the freeze drying temperature is -40° C., and the freeze drying time is 12 h;

[0058] (2) The oxidized nanocellulose is immersed in a copper salt solution, and after the immersion, it is filtered, washed and dried in sequence to obtain a Cu-loaded nanocellulose. 2+ The oxidized nanocellulose is prepared by: the copper salt solution is a copper chloride solution, and the concentration of the copper salt solution is 5 mmol / L; the immersion temperature is 25° C., and the immersion time is 12 h; the washing method is immersing in distilled water for 90 s;

[0059] (3) the acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) 2+ The oxidized nanocellulose is added to a PBS solution containing thrombin and then washed and dried in sequence to obtain a hemostatic material; the acidified oxidized regenerated cellulose and the loaded Cu 2+ The mass ratio of oxidized nanocellulose is 3:1; the concentration of thrombin in the PBS solution containing thrombin is 0.4 g / L; the mixing method is ultrasonic mixing, and the mixing time is 2 hours.

[0060] Example 3

[0061] A method for preparing a hemostatic material comprises the following steps:

[0062] (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid, performing an acidification treatment under stirring conditions, and then filtering, washing and drying in sequence to obtain acidified oxidized regenerated cellulose; the content of the sodium carboxylate structure in the oxidized regenerated cellulose containing a sodium carboxylate structure is 2.0 mmol / g; the molar ratio of the sodium carboxylate structure in the oxidized regenerated cellulose containing a sodium carboxylate structure to the hydrogen ion in the dilute hydrochloric acid is 20:1; the acidification time is 12 h, the acidification temperature is 20° C.; the stirring rate is 300 r / min; the washing method is rinsing with anhydrous ethanol for 2 to 5 times; the drying method is freeze drying; the freeze drying temperature is -40° C., and the freeze drying time is 12 h;

[0063] (2) The oxidized nanocellulose is immersed in a copper salt solution, and after the immersion, it is filtered, washed and dried in sequence to obtain a Cu-loaded nanocellulose. 2+ The oxidized nanocellulose is prepared by: the copper salt solution is a copper chloride solution, and the concentration of the copper salt solution is 8 mmol / L; the immersion temperature is 25° C., and the immersion time is 12 h; the washing method is immersing in distilled water for 90 s;

[0064] (3) the acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) 2+The oxidized nanocellulose is added to a PBS solution containing thrombin and then washed and dried in sequence to obtain a hemostatic material; the acidified oxidized regenerated cellulose and the loaded Cu 2+ The mass ratio of oxidized nanocellulose is 3:1; the concentration of thrombin in the PBS solution containing thrombin is 0.6 g / L; the mixing method is ultrasonic mixing, and the mixing time is 2 hours.

[0065] Comparative Example 1

[0066] A method for preparing a hemostatic material comprises the following steps:

[0067] (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid, performing an acidification treatment under stirring conditions, and then filtering, washing and drying in sequence to obtain acidified oxidized regenerated cellulose; the content of the sodium carboxylate structure in the oxidized regenerated cellulose containing a sodium carboxylate structure is 3.0 mmol / g; the molar ratio of the sodium carboxylate structure in the oxidized regenerated cellulose containing a sodium carboxylate structure to the hydrogen ion in the dilute hydrochloric acid is 35:1; the acidification time is 12 h, the acidification temperature is 20° C.; the stirring rate is 300 r / min; the washing method is rinsing with anhydrous ethanol for 2 to 5 times; the drying method is freeze drying; the freeze drying temperature is -40° C., and the freeze drying time is 12 h;

[0068] (3) The acidified oxidized regenerated cellulose obtained in step (1) is added to a PBS solution containing thrombin, and then washed and dried in sequence to obtain a hemostatic material; the concentration of thrombin in the PBS solution containing thrombin is 0.5 g / L; the mixing method is ultrasonic mixing, and the mixing time is 2 h.

[0069] Comparative Example 2

[0070] A method for preparing a hemostatic material comprises the following steps:

[0071] (1) The oxidized nanocellulose is immersed in a copper salt solution, and then filtered, washed and dried in sequence after the immersion to obtain a Cu-loaded nanocellulose. 2+ The oxidized nanocellulose is prepared by: the copper salt solution is a copper chloride solution, and the concentration of the copper salt solution is 6 mmol / L; the immersion temperature is 25° C., and the immersion time is 12 h; the washing method is immersing in distilled water for 90 s;

[0072] (2) The loaded Cu obtained in step (1) 2+The oxidized nanocellulose is added to a PBS solution containing thrombin, and then washed and dried in sequence to obtain a hemostatic material; the concentration of thrombin in the PBS solution containing thrombin is 0.5 g / L; the mixing method is ultrasonic mixing, and the mixing time is 2 hours.

[0073] Comparative Example 3

[0074] Ordinary sterile gauze.

[0075] The hemostatic properties of the hemostatic materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and the ordinary sterile gauze of Comparative Example 3 were tested. The testing method was as follows: 30 rabbits of the same weight and breed were selected and divided into 6 groups, 5 rabbits in each group. The rabbits were fixed on a dissecting table. After the ear veins of the rabbits were disinfected with medical alcohol, an anesthetic 1% sodium pentobarbital solution (10 mg / kg) was slowly injected. After the rabbits were completely anesthetized, they were disinfected with medical alcohol, and the abdomen was opened. After the abdominal cavity was opened, the tissue fluid and blood on the abdominal cavity and abdominal wall were dried with sterile gauze. Liquid, expose the liver, use a scalpel to make a wound of about 1.5cm×1.5cm×0.3cm in the middle of the liver lobe, and absorb the bleeding with sterilized medical gauze during the wound formation process, then apply the sample to be tested with a size of 2.0cm×2.0cm to the bleeding wound of the liver, and start timing with a stopwatch at the same time, and use a digital camera to record the state and hemostasis process of the sample to be tested before and after hemostasis, and record the hemostasis time after the bleeding wound is completely hemostatic; each material is tested 4 times, and the complete hemostasis time is recorded respectively, and the average value is calculated. The final results are shown in Table 1:

[0076] Table 1 Hemostatic properties of hemostatic materials provided by Examples 1 to 3 and Comparative Examples 1 to 3

[0077]

[0078]

[0079] It can be seen from Table 1 that the hemostatic ability of the hemostatic material prepared by the present invention is greatly improved compared with the existing ordinary sterile gauze, and the hemostatic time is rapidly reduced. When a single group of cellulose is used to prepare the hemostatic material, the required hemostatic time is significantly prolonged, indicating that the present invention further improves the hemostatic performance of the hemostatic material by combining two celluloses.

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a hemostatic material, comprising the following steps: (1) mixing oxidized regenerated cellulose containing a sodium carboxylate structure with dilute hydrochloric acid and performing an acidification treatment to obtain acidified oxidized regenerated cellulose; (2) Immersing the oxidized nanocellulose in a copper salt solution to obtain a Cu-loaded 2+ of oxidized nanocellulose; (3) The acidified oxidized regenerated cellulose obtained in step (1) and the loaded Cu obtained in step (2) are mixed. 2+ The oxidized nanocellulose is added into a PBS solution containing thrombin and mixed, and then washed and dried in sequence to obtain a hemostatic material; The preparation of step (1) and step (2) is not in any particular order; The content of sodium carboxylate structure in the oxidized regenerated cellulose containing sodium carboxylate structure in step (1) is 0.5-5.0 mmol / g; In the step (1), the molar ratio of the sodium carboxylate structure in the oxidized regenerated cellulose containing the sodium carboxylate structure to the hydrogen ions in the dilute hydrochloric acid is (10-50):

1.

2. The preparation method according to claim 1, characterized in that: The acidification treatment time in step (1) is 2 to 48 hours, and the acidification treatment temperature is 10 to 30°C.

3. The preparation method according to claim 1, characterized in that: The copper salt solution in step (2) is a copper chloride solution or a copper sulfate solution, and the concentration of the copper salt solution is 1-10 mmol / L.

4. The preparation method according to claim 1, characterized in that: The immersion temperature in step (2) is 10-30° C., and the immersion time is 6-12 hours.

5. The preparation method according to claim 1, characterized in that: In the step (3), the acidified oxidized regenerated cellulose and the loaded Cu 2+ The mass ratio of oxidized nanocellulose is (1~5):

1.

6. The preparation method according to claim 1, characterized in that: The concentration of thrombin in the PBS solution containing thrombin in step (3) is 0.01-1 g / L.

7. The preparation method according to claim 1, characterized in that: The mixing method in step (3) is ultrasonic mixing, and the mixing time is 0.5 to 6 hours.

8. The hemostatic material prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of effective hemostatic material applicable to open drowning wounds

    CN108379644A

  • Preparation method for generating thrombin loaded oxidization regenerated cellulose hemostasis material through in situ induction

    CN108379648A